2018
DOI: 10.3847/1538-4357/aab891
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Weighted Horizontal Magnetic Gradient Method to a Simulated Flaring Active Region

Abstract: Here, we test the weighted horizontal magnetic gradient (W G M ) as a flare precursor, introduced by Korsós et al. (2015), by applying it to a magnetohydrodynamic (MHD) simulation of solar-like flares (Chatterjee et al. 2016).The pre-flare evolution of the W G M and the behavior of the distance parameter between the area-weighted barycenters of opposite polarity sunspots at various heights is investigated in the simulated δ-type sunspot. Four flares emanated from this sunspot. We found the optimum heights abov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
(53 reference statements)
3
10
0
Order By: Relevance
“…The strong cancellation between the two spots manifests as a series of flare eruptions with magnitudes comparable to GOES C- and B-class events (Korsós et al. 2018 ). Through the creation of a -spot and the flaring activity, they observed the repeated formation of cool dense filaments above the PIL and the ejection of helical flux ropes.…”
Section: Long-term and Large-scale Evolution: Theoretical Aspectsmentioning
confidence: 87%
“…The strong cancellation between the two spots manifests as a series of flare eruptions with magnitudes comparable to GOES C- and B-class events (Korsós et al. 2018 ). Through the creation of a -spot and the flaring activity, they observed the repeated formation of cool dense filaments above the PIL and the ejection of helical flux ropes.…”
Section: Long-term and Large-scale Evolution: Theoretical Aspectsmentioning
confidence: 87%
“…Motivated by the case studies of Korsós et al (2018aKorsós et al ( , 2018b, we now extend the application of the WG M method to more ARs by constructing a data catalog of sunspots using 3D PF and NLFFF extrapolations. An extrapolation example from the collected data catalog is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…They introduced and applied two flare precursors, part of the WG M method (Korsós et al 2019): one is related to the inverted V-shape feature of the WG M proxy and the other is obtained from the U-shape of the so-called distance parameter prior to each investigated flare at a certain height range in the solar atmosphere. Korsós et al (2018a) further conjectured the existence of the so-called optimal height, where the U-shape manifests itself earlier and reaches its minimum value earlier than in the photosphere. In their modeling study it was also shown that these optimal heights agreed reasonably well with the heights of flare occurrence identified by an analysis of thermal and ohmic heating signatures enabled by the magnetohydrodynamic (MHD) simulations of Korsós et al (2018a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations